1995
DOI: 10.1002/ppp.3430060305
|View full text |Cite
|
Sign up to set email alerts
|

Microbial life in permafrost: A historical review

Abstract: This paper reviews the literature on cold-adapted micro-organisms which might exist in ice and permafrost. Properly identified, microbial markers in the cryolithozone could be used in palaeoenvironmental reconstructions, in distinguishing between epigenetic and syngenetic depositional sequences, and in the recognition of secondary thaw unconformities. Cryobiological problems include (1) whether the bacteria are dead, dormant or in the active state, and (2) what factors determine the preservation of cell struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 13 publications
0
44
0
1
Order By: Relevance
“…Forster (1887) was the first to isolate cold-adapted microbes in dead fish preserved by low temperatures. Since then, such microbes have been found in many types of cold environment and extensive reviews have been presented by Morita (1975), Herbert (1986), Gounot (1986, Russel (1990), Friedmann (1994 and Gilichinsky and Wagner (1995). Among other environments, viable microbes were found in permafrost as early as the early twentieth century by Russian scientists investigating Siberian mammoth localities (Omelyansky, 1911) and in buried soils in the Far East (Isachenko, 1912).…”
Section: Cold-adapted Microbesmentioning
confidence: 99%
See 2 more Smart Citations
“…Forster (1887) was the first to isolate cold-adapted microbes in dead fish preserved by low temperatures. Since then, such microbes have been found in many types of cold environment and extensive reviews have been presented by Morita (1975), Herbert (1986), Gounot (1986, Russel (1990), Friedmann (1994 and Gilichinsky and Wagner (1995). Among other environments, viable microbes were found in permafrost as early as the early twentieth century by Russian scientists investigating Siberian mammoth localities (Omelyansky, 1911) and in buried soils in the Far East (Isachenko, 1912).…”
Section: Cold-adapted Microbesmentioning
confidence: 99%
“…Upon thawing, these microbes resumed their physiological activities; a remarkable feat considering the low temperature ((/128C) and the probable great age. Apparently, microbes in permafrost regions tend to accumulate at the bottom of the active layer, as the highest number of microbes is found in the lower part of summer thawing layer in modern tundra soils (Gilichinsky, 1995). Also at the bottom of the previous (7000 Á/9000 cal.…”
Section: Cold-adapted Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that changes in the near-surface soil freeze/thaw status are interrelated, and soil freeze/thaw affects hydrological processes (Cherkauer and Lettenmaier, 1999;Niu and Yang, 2006;Rempel, 2012), ecological processes (Schimel and Mikan, 2005;Tagesson et al, 2012), and soil microbial processes (Lloyd and Taylor, 1994;Gilichinsky and Wagener, 1995;Edwards and Jefferies, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial biomass in permafrost can be quite high with 10 7 to 10 9 cells per gram even in samples that are millions of years old (Gilichinsky and Wagener 1995;Shi, Reeves et al 1997;Vorobyova, Soina et al 1997;Rivkina, Gilichinsky et al 1998;Wilson, Braddock et al 1998). Both aerobic and anaerobic bacteria are present and viable.…”
Section: Fundamental and Applied Research On Water Generated During Pmentioning
confidence: 99%